Development of a Problem-Based Instruction Student Worksheet on Environmental Change to Improve Senior High School Students’ Scientific Literacy - Threesia Anugrah Ilahi; Irdawati; Yuni Ahda; Fitri Arsih; Suci Fajrina (Faculty of Tarbiyah and Teacher Training UIN Jurai Siwo, Lampung, 2025)
This research aims to develop PBI-based student worksheet to improve science literacy and critical thinking of high school grade X students. The research method uses the Plomp Research and Development (R&D) model which consists of initial investigation, design, and evaluation stages. Formative evaluation refers to the Tessmer model, including self-evaluation, expert review, one-to-one, small group, and field test. The instruments used included validation sheets, response questionnaires, and science literacy ability tests. The subjects of the study were 29 students divided into experimental and control classes. The validation results showed that student worksheet was very valid (average score of 87.5%), practical (student and teacher response ≥85%), and effective in improving science literacy. The increase in science literacy gain score was 0.48 (experimental class) and 0.36 (control). The t-test showed significant differences between groups (p < 0.05). Thus, PBI-based student worksheet is suitable for use as a learning medium to improve students' 21st century skills.